Gangguan kesehatann mental menurut perspektif masyarakat - Hidayah, Chusnul Nurul (Maliki Interdisciplinary Journal, 2024)
Mental health is the condition of a person who is free from all indications of mental disorders. Someone who has a healthy mentality will carry out daily activities normally, especially being able to adapt to overcome problems in their life along with the ability to process negative emotions such as stress. Mental health is included in things that require special attention such as physical health. Mental health is not something that is obtained through hereditary genes. This research uses the library search method by comparing the findings and oponions of several authors of books or scientific works. In ordinary society, people with mental health disorders are considered to have strange characteristic and threaten the safety of others , and sufferers are even ostracized by society.